2011
DOI: 10.19030/jabr.v17i3.2081
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Diversification, Manager's Incentive, And Shareholder Wealth

Abstract: <p class="MsoNormal" style="text-align: justify; margin: 0in 37.8pt 0pt 0.5in; mso-pagination: widow-orphan; tab-stops: -4.5pt .5in 1.0in 1.5in 2.0in 2.5in 3.0in 3.5in 4.0in 4.5in 5.0in 5.5in 6.0in;"><span style="font-family: Batang; font-size: x-small;">This study examines the impact of managers' incentives and corporate diversification on the returns to shareholders of acquiring firms in acquisition activities. Managers' incentives are measured by creating an incentive ratio (IR). The IR is const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…(1992). In contrast, this result is inconsistent with the results of walker (2000), Delong (2001), Ueng andwells (2001), Dumontier andPecherot-Petitt (2002), and Martynova and Renneboog (2006). These authors found that the similarity between the activities of corporate bidder and target has a positive impact on the CARs.…”
Section: Multiple Regression Analysismentioning
confidence: 58%
“…(1992). In contrast, this result is inconsistent with the results of walker (2000), Delong (2001), Ueng andwells (2001), Dumontier andPecherot-Petitt (2002), and Martynova and Renneboog (2006). These authors found that the similarity between the activities of corporate bidder and target has a positive impact on the CARs.…”
Section: Multiple Regression Analysismentioning
confidence: 58%
“…As a solution to the agency problem of “the difficulty in monitoring how agent effort influences uncertain outcomes” (Cheng et al , 2015, p. 24), agency theory advocates properly designing executive compensation packages including strong incentives (e.g. equity ownership) (Prendergast, 2002; Cheng et al , 2015) to enhance an executive’s wealth corresponding to the enhanced corporate performance and/or the values of stocks (Baker et al , 1988), and to steer agents’ behavior in serving the best interests of their shareholders (Jensen and Murphy, 1990; Ueng and Wells, 2001; Garas et al , 2022; Kreilkamp et al , 2022; Nkwadi and Matemane, 2022). In summary, the separation of ownership between owners and controllers of companies has necessitated the delegation of power to executives and creation of motivational compensation package to align and take care of various shareholder’s interest.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A common solution to the agency problem inherent in corporate management has been to create executive compensation packages or equity ownership that enhances a managers' wealth in line with increases in corporate performance and/or a firm's stock value (Baker et al, 1988). Ueng and Wells (2001) suggest that both the manager's equity share holdings and whole compensation package should be properly designed to provide a proper incentive for managers for mitigating agency costs.…”
Section: Literature Review 21 Agency Theorymentioning
confidence: 99%